Thrombotic Thrombocytopenic Purpura: When Basic Science Meets Clinical Research - Bécel, Gaëlle; Faict, Sylvia; Picod, Adrien; Bouzid, Raïda; Veyradier, Agnès; Coppo, Paul (Hämostaseologie, 2021)
The therapeutic landscape of thrombotic thrombocytopenic purpura (TTP) is rapidly changing with the recent availability of new targeted therapies. This progressive shift from empiricism to pathophysiology-based treatments reflects an intensive interaction between the continuous findings in the field of basic science and an efficient collaborative clinical research and represents a convincing example of the strength of translational medicine. Despite the rarity of TTP, national and international efforts could circumvent this limitation and shed light on the epidemiology, clinical presentation, prognosis, and long-term outcome of this disease. Importantly, they also provided high-quality results and practice changing studies for the benefit of patients. We report here the most recent therapeutic findings that allowed progressively improving the prognostic of TTP, both at the acute phase and through long-term outcome.
Keywords: plasma exchange; thrombotic thrombocytopenic purpura; thrombotic microangiopathy; rituximab; caplacizumab; ADAMTS13